Entrepreneurial Interest Among Santri within HEBITREN and Its Impact on MSMEs - Asep Maulana Rohimat; Astiti, Rani Dwi; Arifin, Mohammad Rahmawan; Mahmudulhassan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study investigates the factors influencing entrepreneurial interest among students (santri) in Islamic boarding schools (pesantren) affiliated with HEBITREN (Himpunan Ekonomi Bisnis Pesantren, or Pesantren Business Economics Association) in Solo Raya, Central Java, Indonesia. The research identifies three key determinants: self-efficacy, risk tolerance, and environmental conditions. Using a mixed-method approach that integrates quantitative and qualitative analyses, the study surveyed 130 students from two HEBITREN-affiliated institutions: Muhammad Al-Fatih Islamic Boarding School in Sukoharjo and Al-Izzah Islamic Boarding School in Surakarta. The findings highlight self-efficacy as the most significant factor shaping entrepreneurial interest, reinforced by its integration into the educational curriculum and its strong alignment with Islamic values. In contrast, while risk tolerance and community influence contribute, their influence is comparatively marginal. Additionally, the study identifies insufficient entrepreneurial training facilities and limited institutional human resources as barriers to fostering an entrepreneurial mindset among santri. These findings emphasize the need for targeted policy interventions to strengthen the entrepreneurial ecosystem within pesantren, particularly through infrastructure improvements, enhanced self-sufficiency initiatives, and practical entrepreneurial training. This research contributes to the discourse on Islamic education and economic empowerment, providing critical insights for policymakers and educational institutions on the role of pesantren in cultivating future entrepreneurs.